PENENTUAN HARGA PREMI ASURANSI UNIT LINK DENGAN GARANSI MINIMUM - DEWI, NI LUH PUTU RATNA; WIDANA, I NYOMAN; HARINI, LUH PUTU IDA (E-Jurnal Matematika; Vol 8 No 3 (2019), 2019)
The goal of this research is to determine the pricing of unit-linked insurance after attaching the minimum guarantees, which are guaranteed minimum maturity benefit (GMMB) and guaranteed minimum death benefit (GMDB) using the Black-Scholes-Merton Method. Before the new price is determined, the previous steps are find the value of  and  for GMMB or  and   for GMDB. The result of pricing on the cases in this research, resulted if the new price included GMMB with the interest rate 6% and management expenses 0% and 2% are changed from Rp 21.000.000,00 become Rp 21.003.000,00 and Rp 21.031.000,00. On the other hand, the new price for interest rates 14% and 20% with both management expenses are constant. Furthermore, the new price included GMDB with management expense 0% and 2% also interest rates 6%, 14%, and 20% in succession are changed from Rp 21.000.000,00 become Rp 25.132.000,00; Rp 21.031.000,00; Rp 21.002.000,00; Rp 44.521.000,00; Rp 44.520.000,00 and Rp 44.520.000,00.